Emotional Experience of Caam2 in Teaching: Power and Interpretation of Teachers’ Work - Tsang, Kwok K.; Kwong, Tsun L. (Frontiers in Psychology, 2016)
The study explores the social psychological process of teachers’ emotional experiences. Twenty-one secondary schoolteachers in Hong Kong were interviewed. The findings show that the teachers generally felt caam2 (a Cantonese adjective that covers a range of meanings like gloomy, dreadful, tragic, pitiful, pathetic and miserable) in teaching. The social psychological process of the emotional experience of caam2 involves how teachers interpret the significance of their actual work in attaining the teaching goal of making a difference. If they interpret their work as incapable of fulfilling the goal, they will experience negative emotions in teaching. The findings also suggest that the interpretation is affected by teachers’ power which is unequally distributed according to teachers’ teaching experience and managerial roles.